Impact of Financial Ratios on Stock Returns of Industrial Companies in Indonesia - Hidayat, Anggit Yunianto; Zahro, Nafi' Inayati; Handayani, Tri Retno (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
This research aims to examine the influence of return on assets, return on equity, net profit margin, debt-to-equity ratio, and current ratio on stock returns. The population of this study consists of 154 data points from industrial sector companies listed on the Indonesia Stock Exchange between 2018 and 2022. The sampling method used is purposive sampling. After excluding outliers, the sample size is reduced to 52 data points from an initial 60. The analysis method employs multiple linear regression on panel data using Eviews 12 software. The results indicate that return on assets positively affects stock returns, while return on equity and net profit margin negatively affect stock returns. Additionally, the debt-to-equity ratio and current ratio have no significant effect on stock returns.